English Teacher's Strategy in Teaching Writing - Masruroh, Lailatul; Miladiyah, Naziyah (Lingual Journal of Language and Culture, 2023)
One of the English language skills needed by junior high school students to master is writing. The objective of this research is to find out the English teacher’s teaching strategies for teaching writing to seventh graders in SMP Miftahul Ulum Melirang and to describe the responses of students toward the strategy of writing skill of the seventh graders at SMP Miftahul Ulum. The design of the research is qualitative research. The population and sample of this study are English teachers at SMP Miftahul Ulum Melirang. The data collection methods for this study are observation and questioning Based on observation there were four meetings for learning to write, all teaching processes in class used PowerPoint and video as learning media to make the students easier to learn writing. English teachers used strategy in teaching writing by Cox theory (2012). This strategy made students more enthusiastic in learning; there were many good responses from the students. The material taught by the teacher is regarding Descriptive Text (people) and lyrics song; while the media used by the teacher are handbooks, lesson plans, PowerPoint, and videos. Furthermore, the activities in teaching writing consist of opening activities, core activities, and closing activities